2020
DOI: 10.1016/j.cmet.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Serine Catabolism Feeds NADH when Respiration Is Impaired

Abstract: NADH provides electrons for aerobic ATP production. In cells deprived of oxygen or with impaired electron transport chain activity, NADH accumulation can be toxic. To minimize such toxicity, elevated NADH inhibits the classical NADH producing pathways: glucose, glutamine, and fat oxidation. Here, through deuterium tracing studies in cultured cells and mice, we show that folatedependent serine catabolism also produces substantial NADH. Strikingly, when respiration is impaired, serine catabolism through methylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 75 publications
10
135
0
2
Order By: Relevance
“…To examine whether these observations hold in vivo, we infused [U- 13 C]methionine via jugular venous catheter into C57BL/6J mice bearing subcutaneous pancreatic ductal adenocarcinoma (PDAC) allograft tumors [38], achieving an enrichment of 30-60% in serum, tumors and most tissues ( Figure 1D). This extent of labeling is adequate for robust label detection while avoiding severe metabolic perturbation by the labeled methionine infusion.…”
Section: Methionine Comes Mainly From Uptake Rather Than Homocysteinementioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether these observations hold in vivo, we infused [U- 13 C]methionine via jugular venous catheter into C57BL/6J mice bearing subcutaneous pancreatic ductal adenocarcinoma (PDAC) allograft tumors [38], achieving an enrichment of 30-60% in serum, tumors and most tissues ( Figure 1D). This extent of labeling is adequate for robust label detection while avoiding severe metabolic perturbation by the labeled methionine infusion.…”
Section: Methionine Comes Mainly From Uptake Rather Than Homocysteinementioning
confidence: 99%
“…Animal studies were approved and conducted under the supervision of the Princeton University Institutional Animal Care and Use Committee. PDAC tumor tissues derived from LSL-Kras G12D/+ ; LSL-Trp53 R172H/+ ; and Pdx-1-Cre (KPC) mice were used to generate a syngeneic xenograft model, as previously described [38]. Briefly, tumor tissues were minced, mixed with Matrigel (Corning Cat #354234 in 1:1 ratio (v/v)) and injected (200 µL) into the subcutaneous left flank of C57BL/6J mice (Charles River).…”
Section: Mouse Infusion Studiesmentioning
confidence: 99%
“…In a recent study, levels of NADH have been tied to one-carbon metabolism and cellular respiration (Yang, Garcia Canaveras et al, 2020). The TCA cycle as well as the one-carbon metabolism produce NADH in mitochondria; however, only the TCA cycle is regulated by substrate inhibition through NADH.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that mitochondrial FOCM enzymes are particularly strongly upregulated in proliferating lymphocytes and human cancers ( 17 , 69 71 ), which, in part, reflects the role of mitochondrial FOCM in supporting critical cellular functions such as cell proliferation and mitochondrial respiration. Some mitochondrial compartment–specific uses of mitochondrial folate one-carbon units include the local biosynthesis of dTTP ( 20 ) and of N -formylmethionine (fMet) ( 72 ), tRNA modification ( 73 ), oxidative phosphorylation (OXPHOS) complex assembly ( 74 ) and redox state regulation ( 75 , 76 ).…”
Section: Intracellular Compartmentalization Of One-carbon Metabolismmentioning
confidence: 99%
“…Serine catabolism by the mitochondrial folate pathway was also identified as the major source of NAD(H) for cells with impaired electron transport chain activity ( 76 ). In the mitochondria, SHMT2 converts serine to glycine while producing 5,10-methylene-THF.…”
Section: Intracellular Compartmentalization Of One-carbon Metabolismmentioning
confidence: 99%